Mujeres al borde de un ataque de "nervios" [videorecording (DVD)] - Almodóvar, Pedro; Almodóvar, Pedro; Maura, Carmen, 1945-; Barranco, María, 1961-; Serrano, Julieta, 1933-; Banderas, Antonio; Guillén, Fernando, 1931-2013 (MGM Home Entertainment Inc., 2001)
Comedy film about a woman who has been jilted by the love of her life, her friend who discovers her lover is a Shiite terrorist, and her ex-lover's crazed wife.